DEODORIZATION OF ANIMAL FAT - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
D U Omenuko, of ELOFARM, Idemili, Anambra State, Nigeriais one of several readers to have asked CTA's Question and Answer service recently about removing the smell from fats and oil, to boost their marketability as cooking oils and for soap...